Motions of a connected subgraph representing a swarm of robots inside a graph of work stations - Aarón Atilano; Christian Rubio-Montiel; Sebastian Bejos (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
Imagine that a swarm of robots is given, these robots must communicate with each other, and they can do so if certain conditions are met. We say that the swarm is connected if there is at least one way to send a message between each pair of robots. A robot can move from a work station to another only if the connectivity of the swarm is preserved in order to perform some tasks. We model the problem via graph theory, we study connected subgraphs and how to motion them inside a connected graph preserving the connectivity. We determine completely the group of movements.